Towards the global abolition of the death penalty: comparing the criminal law in the United States of America and Nigeria (2007)
This article begins with a short history of the punishment of death and highlights the methods by which it is carried out. It then discusses the death penalty from a global perspective with emphasis on Nigeria and the United State of America, and considers recent trends towards its abolition. The international and national efforts towards the abolition of the death penalty are examined. The article concludes that the global move towards abolition of death penalty is a move in the right direction